Disclosure of HIV test results by women to their partners following antenatal HIV testing: - Batte, Anthony; Katahoire, Anne Ruhweza; Chimoyi, Anne; Ajambo, Susan; Tibingana, Brenda; Tibingana, Brenda; Banura, Cecily (BMC Public Health, 2015)
Abstract Background: Disclosure of HIV status by women to their partners is the backbone for prevention of HIV transmission among couples as well as promotion of the prevention of mother to child transmission of HIV interventions. The aim of this study was to determine the prevalence and factors associated with disclosure of HIV test results by women to their sexual partners following antenatal HIV testing in Kamwokya slum community, Kampala, Uganda. Methods: This was a population based cross-sectional study carried out from October to November 2011. A total of 408 randomly selected women aged 18–45 years, who had delivered a child within 2 years prior to the study, and had tested for HIV during antenatal care were recruited from Kamwokya community. A standardised interviewer- administered questionnaire was used to collect data. Data was entered into Epidata 2.1b and analysed using SPSS software version 16.0 and StatsDirect version 2.8.0. Results: Overall 83.8% (95% CI: 79.9- 87.1) of the women reported that they had disclosed their HIV status to their sexual partners. Disclosure was significantly higher among women whose partners had also tested for HIV (OR=24.86, 95% CI: 5.30 - 116.56). Other factors that were associated with disclosure were secondary education or above (OR=2.66, 95% CI: 1.34 - 5.30), having attended 3 or more antenatal care visits (OR=3.62, 95% CI: 1.70 - 7.72), being married/cohabiting (OR=8.76, 95% CI: 4.06 - 18.81) and whether or not they would opt not to disclose a family member’s HIV status (OR=1.61, 95% CI: 1.003 - 2.58). Overall, stigma was not significantly associated with disclosure. Conclusions: Disclosure of HIV test results to sexual partners in this group of women was relatively high. The results suggest that having a sexual partner who had also tested probably made it easier to disclose the woman’s HIV status. Other predictors of disclosure were secondary education and above and having attended more antenatal care visits. These findings suggest the need for promotion of sexual partner HIV testing, improvement of literacy levels of women, and encouragement of women to attend antenatal care, as key factors in promoting disclosure of HIV results
a population-based cross-sectional survey among slum dwellers in Kampala Uganda
Keywords: HIV; Women; Antenatal; Slum dwellers; Uganda